Les territoires de l’alcool à Tunis et à Casablanca sous la période des Protectorats (1912-1956) : Des destins parallèles ? - Nessim Znaien (L’Année du Maghreb)
Based on administrative, judicial and police sources we attempted to explore the territories of alcohol marketing and consumption in Tunis and Casablanca during the period of the French Protectorates in Tunisia (1881-1956) and Morocco (1912 -1956). The purpose of this article is to show that both cities experienced, during the period of the Protectorate, a change in alcohol consumption practices, resulting in a larger increase in alcohol consumption and the emergence of a new public debate, exemplified by prohibitionist laws.During the interwar period, Tunis and Casablanca were, within their respective countries, the largest centers of drinking establishments, with a dramatic increase in alcohol supply. Social codes with regard to drinking (place, time and consumption sociability) retained their own logic in relation to mainland France, partly due to religious factors. At a more local level, administrative sources indicate that alcohol sales networks (cafes, bars, wine cellars) seemed to conform in both cities to strict discontinuity between the colonial city and the Medina - in theory, though not so much in practice.Finally, the frequency of measures taken on alcohol regulation was about the same in Tunisia and Morocco. The years 1913-1914 and 1936-1937 seemed to be key moments. This chronology, specific to North African colonies, reflects more the Empire’s comprehensive management policies set forth by the French at that time.